2008
DOI: 10.1097/01.phh.0000338377.83736.9c
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Web-Based Integrated Birth Defects Surveillance System in New York State

Abstract: The CMR's Web-based integrated birth defects surveillance system empowers authorized users to perform routine surveillance activities using only a PC and a Web browser. This system will help NYS public health professionals and epidemiologists perform trend analyses and identify possible clusters of birth defects in space and time that may be related to environmental toxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…The successful geocoding rate of 88.5% is comparable to other studies that involve geocoding birth certificate data (27, 28). However, a significantly lower proportion of successful geocoded addresses among the rural population was not optimal.…”
Section: Discussionsupporting
confidence: 77%
“…The successful geocoding rate of 88.5% is comparable to other studies that involve geocoding birth certificate data (27, 28). However, a significantly lower proportion of successful geocoded addresses among the rural population was not optimal.…”
Section: Discussionsupporting
confidence: 77%
“…Aside from geocoding (Forand et al, 2002;Gilboa et al, 2006, GIS techniques have been used in birth defects research in a variety of ways, such as determining prevalence, risk factors (e.g., socioeconomic status and living near hazardous sites), access to health care, and mapping the spatial distribution of birth defects (Rushton and Lolonis, 1998;Wasserman et al, 1998;Siffel et al, 2006;Gardner et al, 2007;Case et al, 2008;Langlois et al, 2009a,b;Luben et al, 2009;Messer et al, 2010;Wang et al, 2010a;Root et al, 2011;Fixler et al, 2012;Colvin et al, 2013). Aday and Andersen (1974) suggested that "access" needed to be measured in terms of whether the population with health care needs is able to enter the medical system, a concept also known as "realized" access (Khan and Bhardwaj, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Web-based registries have been previously established in other fields of medicine 256. Most involve conversion of existing manual and computer-based registries to web-based registries.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the web-based approach overcomes data management issues and allows for periodic generation of information for monitoring and policy making. Health managers at hospitals, national, and international levels use web-based registries to compile information on different health issues 567…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation